2014
DOI: 10.1158/1078-0432.ccr-13-2782
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements of Tumoral p95HER2 Protein Expression in Metastatic Breast Cancer Patients Treated with Trastuzumab: Independent Validation of the p95HER2 Clinical Cutoff

Abstract: Purpose: P95HER2 (p95) is a truncated form of the HER2, which lacks the trastuzumab-binding site and contains a hyperactive kinase domain. Previously, an optimal clinical cutoff of p95 expression for progression-free survival (PFS) and overall survival (OS) was defined using a quantitative VeraTag assay (Monogram Biosciences) in a training set of trastuzumab-treated metastatic breast cancer (MBC) patients.Experimental Design: In the current study, the predictive value of the p95 VeraTag assay cutoff establishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 18 publications
3
41
1
Order By: Relevance
“…Elevated serum levels of the HER2 ECD in breast cancer patients have been correlated with HER2 gene amplification, metastasis, and poor survival [94][95][96]. Increased levels of the p95HER2 variant have been correlated with poor prognosis and trastuzumab resistance in HER2 positive breast cancer [73,75,[97][98][99]. Preclinical in vitro and in vivo studies demonstrated that p95HER2 exhibited kinase activity that induced tumor proliferation that was resistant to trastuzumab therapy [71,73,75,90].…”
Section: Her2 Structural Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum levels of the HER2 ECD in breast cancer patients have been correlated with HER2 gene amplification, metastasis, and poor survival [94][95][96]. Increased levels of the p95HER2 variant have been correlated with poor prognosis and trastuzumab resistance in HER2 positive breast cancer [73,75,[97][98][99]. Preclinical in vitro and in vivo studies demonstrated that p95HER2 exhibited kinase activity that induced tumor proliferation that was resistant to trastuzumab therapy [71,73,75,90].…”
Section: Her2 Structural Alterationmentioning
confidence: 99%
“…Some early results have validated specific cutoff levels of expression that can be assayed in a clinical trial setting [97,108]. In contrast to reports showing resistance to trastuzumab as a single agent, early reports from the GeparQuattro and www.TheOncologist.com [109].…”
Section: Her2 Structural Alterationmentioning
confidence: 99%
“…In contrast, in the metastatic setting, p95HER2 has been found to negatively correlate with PFS and OS (23). It is possible that this difference could be due to phenotypic differences in the primary and metastatic tumors, especially under selective pressure of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This C-terminal fragment of HER2, called p95HER2 for its molecular weight by Western blot analysis, is constitutively active, highly tumorigenic, and has been shown to correlate with intrinsic resistance to trastuzumab-based therapy in the metastatic setting (20)(21)(22)(23). Recent data based on p95HER2 evaluation by immunohistochemistry in the neoadjuvant setting, however, showed the opposite trend, correlating the expression of this truncated form with response to trastuzumabbased treatment (24).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies directed towards HER2, such as trastuzumab, cannot bind in the absence of the ECD. Several retrospective analyses of HER2 positive breast cancer found that increased p95HER2 expression correlated with resistance to trastuzumab therapy and poor survival [19,20]. Preclinical in vitro and in vivo studies demonstrated that p95HER2 exhibited kinase activity that induced tumor proliferation that was resistant to trastuzumab therapy [18,19,21].…”
Section: Introductionmentioning
confidence: 99%